Interlayer in-situ modification method for composite material based on short fibers and polyurethane
By introducing short carbon fibers and polyurethane into the epoxy resin and synergistically modifying the epoxy resin, the problems of insufficient inter-layer fracture toughness and shear strength of the low-temperature storage tank are solved, significantly improving the inter-layer performance of the laminate, and meeting the application needs of low-temperature storage tanks.
Patent Information
- Application Number
- CN202411850668.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-16
AI Technical Summary
Low-temperature storage tanks are prone to early microcracks under the conditions of hot and cold circulation, causing the cracks to span multiple layers and form a complete path for propellant leakage, which in turn poses huge risks to the interlayer areas of the laminate.
The interlayer in-situ modification method based on the composite material based on short fiber and polyurethane is adopted. By introducing short carbon fibers and polyurethane into the epoxy resin, the epoxy resin is synergistically modified to improve the interlayer fracture toughness and shear strength.
The interlayer fracture toughness and shear strength of continuous carbon fiber reinforced epoxy composite laminates is significantly improved, the risk of interlayer layer expansion is reduced, and the need for interlayer performance of laminates is met in the low-temperature storage tank.
Smart Images

Figure CN119636114A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resin material modification, in particular to an in-situ modification method for composite materials based on short fibers and polyurethane. Background Art
[0002] Epoxy resins are thermosetting materials with multidisciplinary application potential. They are widely used in construction, electronic instruments, adhesives and composite matrices due to their excellent dimensional stability, good mechanical properties and high chemical resistance.
[0003] Continuous carbon fiber reinforced epoxy composite laminates show satisfactory weight reduction efficiency and economic advantages in heavy-duty space launch vehicles, especially in cryogenic tank applications, due to their excellent specific stiffness and strength.
[0004] However, the hot and cold cycle conditions of cryogenic tanks (room temperature when empty and low temperature when storing cryogenic propellants) will result in extreme thermal coupling effects, which will lead to the initiation of early microcracks. Subsequently, the cracks will cross multiple layers and eventually form a complete path for propellant leakage, posing a huge risk to the interlayer area of the laminate.
[0005] In addition, in laminates, the interlaminar region between the layers is rich in epoxy resin matrix, and interlaminar damage such as delamination has always been one of the main failure modes of laminate structures. Therefore, in the past decade, how to improve the interlaminar fracture toughness and shear strength of laminates has been a key issue that many scholars and engineering designers have paid attention to.
[0006] Therefore, a new solution to the above problems needs to be proposed. Summary of the invention
[0007] The purpose of the present invention is to provide an in-situ modification method for composite layers based on short fibers and polyurethane to solve the technical problems raised in the background technology.
[0008] To achieve the above object, the present invention provides the following technical solution: a method for in-situ modification of composite materials based on short fibers and polyurethane, comprising at least the following steps:
[0009] S1: Prepare a sufficient amount of carbon fiber cloth for preparing a continuous fiber reinforced epoxy composite laminate;
[0010] S2: After the epoxy resin is fully preheated in the heating jacket, the polyurethane is added according to the required mass ratio and stirred thoroughly to mix evenly, and then the required amount of short carbon fibers is added and stirred until evenly mixed, and then the curing agent is added according to the required mass ratio and stirred evenly;
[0011] S3: After placing the mixture in a vacuum oven to remove bubbles, the mixture is evenly coated on the surface of the fiber cloth;
[0012] S4: After laying the layers according to the required thickness, put them into a hot press for hot pressing.
[0013] Furthermore, the carbon fiber model of the carbon fiber cloth and the short carbon fiber in S1 is T300.
[0014] Furthermore, the epoxy resin in S2 is bisphenol A epoxy resin (E51) with an epoxy equivalent of 186 g / mol.
[0015] Furthermore, the temperature of the heating jacket in S2 is 110°C.
[0016] Furthermore, the active group content of the polyurethane in S2 is 0.08±0.02, and the mass ratio of the polyurethane to the epoxy resin is 1:20 (5 phr).
[0017] Furthermore, the mass fraction of the short carbon fibers added to S2 is 0% to 0.075%, and the stirring time is 30 minutes.
[0018] Furthermore, the curing agent in S2 is 4,4'-diaminodiphenyl sulfone (DDS), and the mass ratio of the curing agent to the epoxy resin is 34:100 (34 phr).
[0019] Furthermore, the temperature of the vacuum oven in S3 is 110°C.
[0020] Furthermore, the heating program of the hot press in S4 is as follows: heating to 100°C and keeping warm for 0.5h, heating to 130°C and keeping warm for 1h, heating to 160°C and keeping warm for 1.5h, heating to 180°C and keeping warm for 1h, and the heating rate is 2°C / min.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention improves the interlayer performance of continuous carbon fiber reinforced epoxy composite laminates by simultaneously introducing short carbon fibers and polyurethane into epoxy resins for synergistic modification. Short carbon fibers can improve the mechanical properties of epoxy resins due to their excellent mechanical properties, thereby improving interlayer fracture strength. At the same time, the fiber bridging effect can be used to inhibit interlayer delamination and increase energy dissipation, thereby improving interlayer fracture toughness. On the other hand, polyurethane can be used as a plasticizer to achieve a toughening effect on epoxy resins and improve interlayer fracture toughness. Since the toughening mechanisms of the two are different and their simultaneous addition has a synergistic effect, the interlayer performance of the laminates can be significantly enhanced, and their interlayer fracture strength and fracture toughness are significantly better than those of unmodified laminates.
[0023] 2. The method proposed in the present invention directly introduces short carbon fibers and polyurethane into epoxy resin, which can conveniently adjust the thickness of the laminate. The preparation process is simple and the cost is low. At the same time, the interlayer performance of continuous carbon fiber reinforced epoxy composites is comprehensively improved to meet the requirements of low-temperature storage tanks for the interlayer performance of laminates. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0025] Figure 1 This is a performance diagram of interlaminar fracture strength of the laminate prepared by the present invention;
[0026] Figure 2 This is a performance diagram of interlaminar fracture toughness of the laminate prepared by the present invention;
[0027] Figure 3 Schematic diagram of the laminate layer prepared by the present invention. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0029] The design process of the present invention is:
[0030] Considering that epoxy resin has a highly cross-linked spatial network structure, its own brittleness will seriously limit its application in engineering. Therefore, it is particularly important to improve its toughness and enhance its comprehensive mechanical properties. Polyurethane is formed by the addition polymerization of polyisocyanate and polyhydroxy polymer. It is a polymer compound containing many repeated urethane segments (-NHCOO-) on the polymer main chain. Polyurethane can be regarded as a kind of thermoplastic resin. It has the advantages of high plasticity, high elasticity, low temperature resistance and good chemical compatibility. It is an attractive toughening agent. It has a large number of polar groups and can be connected with epoxy resin through covalent bonds and hydrogen bonds to form an interpenetrating or semi-interpenetrating polymer network. Its synthesis, reaction mechanism, morphology and mechanical properties have received extensive attention and research. The main chain of polyurethane molecules is composed of flexible long-chain polyols and rigid isocyanate blocks, which can effectively disperse stress, and the widespread hydrogen bonding inside it further improves the mechanical properties of the material. In addition, polyurethane toughened epoxy resin has a special phase separation phenomenon. A large number of studies have shown that only when the thermoplastic resin undergoes phase separation in the matrix can the toughness of the epoxy resin be significantly increased. In addition, the phase separation formation process of polyurethane and epoxy resin and its strengthening and toughening mechanism for epoxy resin have been fully studied, so it is considered to introduce polyurethane into epoxy resin as a toughening agent.
[0031] Since the mechanical properties of epoxy resin itself are relatively low, the present invention considers directly introducing high-strength discrete short carbon fibers into epoxy resin to achieve in-situ reinforcement effect without adding additional intermediate layers in the laminate to improve its interlaminar fracture strength. The incorporated short carbon fibers are expected to be discretely distributed in the resin-rich areas between the layers, which will theoretically improve the inherent mechanical properties of the epoxy resin while inducing more interlaminar bridging fibers, thereby effectively inhibiting the subsequent interlaminar delamination expansion and increasing energy dissipation, and thus can also play a role in toughening.
[0032] See also Figure 3 , and then proposed a method for in-situ modification of composite layers based on short fibers and polyurethane:
[0033] Prepare a sufficient amount of carbon fiber cloth for preparing continuous fiber reinforced epoxy composite laminates;
[0034] After the epoxy resin is fully preheated in the heating jacket, the polyurethane is added according to the required mass ratio and stirred thoroughly to mix evenly, then the required amount of short carbon fibers is added and stirred until evenly mixed, and then the curing agent is added according to the required mass ratio and stirred evenly;
[0035] After placing the mixture in a vacuum oven to remove air bubbles, the mixture is evenly coated on the surface of the fiber cloth;
[0036] After laying the layers according to the required thickness, they are placed in a hot press and hot pressed into shape.
[0037] See the following embodiments for details:
[0038] Example 1
[0039] A sufficient amount of T300 carbon fiber cloth (10 layers of carbon fiber cloth for the interlaminar fracture strength test and 18 layers of carbon fiber cloth for the interlaminar fracture toughness test) was prepared for preparing continuous fiber reinforced epoxy composite laminates.
[0040] After the E-51 epoxy resin was fully preheated in a heating mantle at 110° C., the curing agent was added to the epoxy resin at a mass ratio of curing agent to epoxy resin of 34:100 (34 phr) and stirred evenly.
[0041] After the mixture was placed in a vacuum oven at 110°C to remove bubbles, the mixture was evenly coated on the surface of the fiber cloth.
[0042] After laying the layers according to the required thickness (2mm for interlaminar fracture strength test and 3mm for interlaminar fracture toughness test), they are placed in a hot press for hot pressing. The heating program of the hot press is set to 100℃ for 0.5h, 130℃ for 1h, 160℃ for 1.5h and 180℃ for 1h.
[0043] The interlayer performance of the prepared laminate was tested according to the ASTM D2344 test standard, such as Figure 1 As shown, the interlaminar rupture strength of the laminate is 51.7MPa. According to the ASTM D5528 test standard, Figure 2 As shown in Figure 2, the initial and stable values of interlaminar fracture toughness of the laminate are 269.0 J / m 2 and 363.5 J / m 2 .
[0044] Example 2
[0045] A sufficient amount of T300 carbon fiber cloth (10 layers of carbon fiber cloth for the interlaminar fracture strength test and 18 layers of carbon fiber cloth for the interlaminar fracture toughness test) was prepared for preparing continuous fiber reinforced epoxy composite laminates.
[0046] After the E-51 epoxy resin was fully preheated in a heating jacket at 110°C, short carbon fibers with a mass fraction of 0.075% were added and stirred for 30 minutes until uniformly mixed. The curing agent was added to the epoxy resin at a mass ratio of curing agent to epoxy resin of 34:100 (34 phr) and stirred uniformly.
[0047] After the mixture was placed in a vacuum oven at 110°C to remove bubbles, the mixture was evenly coated on the surface of the fiber cloth.
[0048] After laying the layers according to the required thickness (2mm for interlaminar fracture strength test and 3mm for interlaminar fracture toughness test), they are placed in a hot press for hot pressing. The heating program of the hot press is set to 100℃ for 0.5h, 130℃ for 1h, 160℃ for 1.5h and 180℃ for 1h.
[0049] The interlayer performance of the prepared laminate was tested according to the ASTM D2344 test standard, such as Figure 1 As shown, the interlaminar rupture strength of the laminate is 60.7MPa. According to the ASTM D5528 test standard, Figure 2 As shown in Figure 2, the initial and stable values of interlaminar fracture toughness of the laminate are 313.5 J / m 2 and 467.1 J / m 2 .
[0050] Example 3
[0051] A sufficient amount of T300 carbon fiber cloth (10 layers of carbon fiber cloth for the interlaminar fracture strength test and 18 layers of carbon fiber cloth for the interlaminar fracture toughness test) was prepared for preparing continuous fiber reinforced epoxy composite laminates.
[0052] After the E-51 epoxy resin was fully preheated in a heating jacket at 110°C, polyurethane was added to the epoxy resin at a mass ratio of polyurethane to epoxy resin of 1:20 (5phr) and stirred evenly, and then curing agent was added to the epoxy resin at a mass ratio of curing agent to epoxy resin of 34:100 (34phr) and stirred evenly.
[0053] After the mixture was placed in a vacuum oven at 110°C to remove bubbles, the mixture was evenly coated on the surface of the fiber cloth.
[0054] After laying the layers according to the required thickness (2mm for interlaminar fracture strength test and 3mm for interlaminar fracture toughness test), they are placed in a hot press for hot pressing. The heating program of the hot press is set to 100℃ for 0.5h, 130℃ for 1h, 160℃ for 1.5h and 180℃ for 1h.
[0055] The interlayer performance of the prepared laminate was tested according to the ASTM D2344 test standard, such as Figure 1 As shown, the interlaminar rupture strength of the laminate is 60.7MPa. According to the ASTM D5528 test standard, Figure 2 As shown in Figure 2, the initial and stable values of interlaminar fracture toughness of the laminate are 322.7 J / m 2 and 423.6 J / m 2 .
[0056] Example 4
[0057] A sufficient amount of T300 carbon fiber cloth (10 layers of carbon fiber cloth for the interlaminar fracture strength test and 18 layers of carbon fiber cloth for the interlaminar fracture toughness test) was prepared for preparing continuous fiber reinforced epoxy composite laminates.
[0058] After the E-51 epoxy resin was fully preheated in a heating jacket at 110°C, polyurethane was added to the epoxy resin at a mass ratio of 1:20 (5phr) of polyurethane:epoxy resin and stirred evenly, and then short carbon fibers with a mass fraction of 0.075% were added and stirred for 30 minutes until they were evenly stirred, and curing agent was added to the epoxy resin at a mass ratio of 34:100 (34phr) of curing agent:epoxy resin and stirred evenly.
[0059] After the mixture was placed in a vacuum oven at 110°C to remove bubbles, the mixture was evenly coated on the surface of the fiber cloth.
[0060] After laying the layers according to the required thickness (2mm for interlaminar fracture strength test and 3mm for interlaminar fracture toughness test), they are placed in a hot press for hot pressing. The heating program of the hot press is set to 100℃ for 0.5h, 130℃ for 1h, 160℃ for 1.5h and 180℃ for 1h.
[0061] The interlayer performance of the prepared laminate was tested according to the ASTM D2344 test standard, such as Figure 1 As shown, the interlaminar rupture strength of the laminate is 66.6MPa. According to the ASTM D5528 test standard, Figure 2 As shown in Figure 2, the initial and stable values of interlaminar fracture toughness of the laminate are 384.7 J / m 2 and 551.3 J / m 2 .
[0062] In summary: The present invention utilizes discrete short carbon fibers and microphase separation polyurethane to synergistically modify epoxy resin, thereby enhancing the interlaminar performance of toughened continuous carbon fiber reinforced epoxy composite laminates. The epoxy resin is toughened by adding microphase separation polyurethane, thereby improving the interlaminar fracture toughness of the composite material. In addition, an appropriate amount of discrete short carbon fibers is added to the epoxy resin, and the high-strength characteristics of the short carbon fibers are utilized to improve the interlaminar shear strength of the composite material. The method of the present invention not only has the advantages of easy thickness control, simple operation and low cost, but also can comprehensively improve the interlaminar performance of continuous carbon fiber reinforced epoxy composites, and can meet the requirements of engineering applications in the aerospace field for interlaminar performance of laminates.
[0063] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for in-situ modification of composite materials based on short fibers and polyurethane, characterized in that: At least the following steps are included: S1: Prepare a sufficient amount of carbon fiber cloth for preparing a continuous fiber reinforced epoxy composite laminate; S2: After the epoxy resin is fully preheated in the heating jacket, the polyurethane is added according to the required mass ratio and stirred thoroughly to mix evenly, and then the required amount of short carbon fibers is added and stirred until evenly mixed, and then the curing agent is added according to the required mass ratio and stirred evenly; S3: After placing the mixture in a vacuum oven to remove bubbles, the mixture is evenly coated on the surface of the fiber cloth; S4: After laying the layers according to the required thickness, put them into a hot press for hot pressing.
2. The in-situ modification method of composite material layers based on short fibers and polyurethane according to claim 1, characterized in that: The carbon fiber model of the carbon fiber cloth and short carbon fiber in the S1 is T300.
3. The in-situ modification method of composite material layers based on short fibers and polyurethane according to claim 1, characterized in that: The epoxy resin in S2 is bisphenol A epoxy resin (E51) with an epoxy equivalent of 186 g / mol.
4. The in-situ modification method of composite material layers based on short fibers and polyurethane according to claim 1, characterized in that: The temperature of the heating jacket in S2 is 110°C.
5. The in-situ modification method of composite materials based on short fibers and polyurethane according to claim 1, characterized in that: The active group content of the polyurethane in the S2 is 0.08±0.02, and the mass ratio of the polyurethane to the epoxy resin is 1:
20.
6. The in-situ modification method of composite materials based on short fibers and polyurethane according to claim 1, characterized in that: The mass fraction of the short carbon fibers added to S2 is 0% to 0.075%, and the stirring time is 30 minutes.
7. The in-situ modification method for composite materials based on short fibers and polyurethane according to claim 1, characterized in that: The curing agent in S2 is 4,4'-diaminodiphenyl sulfone (DDS), and the mass ratio of the curing agent to the epoxy resin is 34:
100.
8. The in-situ modification method for composite materials based on short fibers and polyurethane according to claim 1, characterized in that: The temperature of the vacuum oven in S3 is 110°C.
9. The in-situ modification method for composite materials based on short fibers and polyurethane according to claim 1, characterized in that: The heating program of the hot press in S4 is to heat to 100°C and keep warm for 0.5h, heat to 130°C and keep warm for 1h, heat to 160°C and keep warm for 1.5h, heat to 180°C and keep warm for 1h, and the heating rate is 2°C / min.
Citation Information
Patent Citations
Modified epoxy resin base material and modified epoxy resin matrix composite material
CN102617984A
Manufacturing method of composite material laminated plate with holes
CN103496173A
Manufacturing method of non-woven fabric seal gasket
CN103640232A
Preparation method for ultra high molecular weight polyethylene (UHMWPE) fiber / thermosetting epoxy resin high-strength anti-bending composite board
CN107486954A
Sandwich structure, molded object, and production processes therefor
CN108290374A